2007
DOI: 10.1063/1.2731707
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of N:H codoping effect on energy gap narrowing of TiO2

Abstract: The energy band structures and density of states for N-doped and N:H-doped anatase TiO 2 are calculated based on the first-principles density-functional theory. For N-doped TiO 2 , there appear two isolated states above the top of the valence band and the band gap narrowing is very small. With the same nitrogen dopant concentration, N:H doping yields a significant band gap narrowing. The calculated results support our experimental data that N:H-doped TiO 2 exhibited higher visible-light photocatalytic efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 28 publications
(19 reference statements)
5
39
0
Order By: Relevance
“…From Figure 4, we can see clearly that with the decrease of the electronegativity difference between oxygen and substitutional elements, (N, C, and B), the impurity states become closer to the VBM. In addition, when the charges are balanced, the electron donors (H) may contribute to the lowering of the energy levels related to the acceptors (N, C, and B), resulting in the impurity states downward to the VBM, which agrees well with the previous studies [40]. Accordingly, the N : H species may enhance the mixing of impurity states induced by N 2p states and O 2p atomic orbitals in the VBM, and finally new valence bands can be formed, which could contribute to the formation of the band-band transition, in favor of the visible-light-driven catalytic activities.…”
Section: Effect Of Charge Balance On the Electronic Structuressupporting
confidence: 81%
“…From Figure 4, we can see clearly that with the decrease of the electronegativity difference between oxygen and substitutional elements, (N, C, and B), the impurity states become closer to the VBM. In addition, when the charges are balanced, the electron donors (H) may contribute to the lowering of the energy levels related to the acceptors (N, C, and B), resulting in the impurity states downward to the VBM, which agrees well with the previous studies [40]. Accordingly, the N : H species may enhance the mixing of impurity states induced by N 2p states and O 2p atomic orbitals in the VBM, and finally new valence bands can be formed, which could contribute to the formation of the band-band transition, in favor of the visible-light-driven catalytic activities.…”
Section: Effect Of Charge Balance On the Electronic Structuressupporting
confidence: 81%
“…Theoretical investigations have also been carried out to study the band structures of TiO 2 phases including anatase [13][14][15] and rutile [16][17][18][19][20]. Mo, as a transition metal, has been used to dope TiO 2 for photocatalytic applications, showing the effects to make the materials catalytically active under visible light [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, Mi and his co-workers reported that N/Hcodoped TiO 2 shows higher photocatalytic activity than those of both N-doped anatase TiO 2 and pure TiO 2 . 18 Alvaro reported that the photocatalytic activity of TiO 2 can be enhanced by complexation with organic additives. 19 Moreover, Davies et al reported that the C-H bond has a significant effect on photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%